Silymarin nanoemulsion against human hepatocellular carcinoma: development and optimization. (17th February 2018) - Ahmad, Usama; Akhtar, Juber; Singh, Satya Prakash; , Badruddeen; Ahmad, Farhan Jalees; Siddiqui, Sahabjada; , Wahajuddin
Abstract: Objective: Nanoemulsion of silymarin was developed and optimized. Materials and methods: Nanoemulsion was made by aqueous titration method. Sefsol 218 (5.8% v/v), Kolliphor RH40 and polyethylene glycol 400 ( S mix ; 2:1; 28.99% v/v) were used as oil phase, surfactant and co-surfactant while distilled water (65.22% v/v) acted as an aqueous phase. Nanoemulsion was characterized on the basis of particle size, viscosity, electrical conductivity and refractive index. Further, in vitro release, in vivo pharmacokinetic study, stability study and cancer cell line studies were also performed. Results and discussion: The optimized formulation (NE9) with mean particle size of 21.24 nm showed a minimum viscosity of 9.59 cps, maximum drug release (97.75%) in 24 h. The NE9 formulation also showed higher AUC ( p < .01) and C max ( p < .01) and shorter T max ( p < .05) compared with conventional and standard suspensions of silymarin. The stability study also showed considerably stable formulations at refrigerator temperature as compared with room temperature ( p > .05). The cancer cell line studies also confirmed that silymarin nanoemulsion reduced the cell viability and increased ROS intensity and chromatin condensation ( p < .05). Conclusion: Our results concluded that nanoemulsion may be an efficient carrier for oral delivery of silymarin against human hepatocellular carcinoma without damaging normal cells.